The relationship between resting heart rate variability and sportive performance, sleep and body awareness in soccer players - Tekin, R. T.; Kudas, S.; Buran, M. M.; Cabuk, S.; Akbasli, O.; Uludag, V.; Yosmaoglu, H. B. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Heart rate variability (HRV) is a key marker of autonomic nervous system function and has been proposed as a tool for monitoring training adaptations. However, its relationship with performance beyond aerobic capacity remains unclear in football players. This study aimed to examine the associations between resting HRV and aerobic capacity, agility, neuromuscular coordination, sleep quality, and body awareness.